Fermentasi Bunga Telang (Clitoria ternatea L) Dengan Penambahan Madu Baduy Produk SR12 Sebagai Inovasi Bioteknologi Kombucha - Mu'jijah Mu'jijah; Nurullah Asep Abdilah; Firman Rezaldi; Kusumiyati Kusumiyati; Diyan Yunanto Setyaji; M Fariz Fadillah (Fakultas Matematika & Ilmu Pengetahuan Alam - Universitas Islam Malang, 2023)
Gram positive and negative bacteria have always been a problem for the survival of living things in a high threshold as normal flora. Telang flower contains anthocyanins which are efficacious as antioxidants and antibacterials so that kombucha has a high potential to be fermented by kombucha as the latest biotechnology product innovation in improving the immune system with the addition of a concentration of Baduy honey Product SR12 which has the potential to inhibit the growth of pathogens. This study aims to produce information regarding the concentration of Baduy honey product SR12 which has the potential as a gram-positive and gram-negative antibacterial. The research design used was a randomized block design which was divided into 2 factors. Factor I is the Concentration of Telang Flower Kombucha Sugar (Clitoria ternatea L) solution in the first fermentation (20%, 30%, and 40%) and factor II is the concentration of baduy honey product SR12, namely (20%, 30%, and 40%). Each treatment was repeated 3 times. The results obtained were processed using statistical analysis using one-way ANOVA at the 95% level. If the data from the research results have significant differences, ideally it can be followed up using a post hoc test. The results obtained in this study were the concentration of Baduy honey Product SR12 was positively correlated in preventing the growth of pathogens in both gram-positive and gram-negative bacteria. The conclusion in this study is that kombucha flower telang has the ability as a gram positive and negative antibacterial and can also be developed as the latest biotechnology product innovation. Telang flower kombucha fermentation with a concentration of Baduy honey Product SR12 of 40% had the highest antibacterial activity when compared to fermented telang flower kombucha at concentrations of Baduy honey Product SR12 with a concentration of 20% and 30%. The average diameter of the inhibition zone produced by Staphylococcus aureus bacteria is 20.08 mm in the strong category, Staphylococcus epidermidis 17.98 mm in the strong category, Pseudomonas aeruginosa 17.27 mm in the strong category, and Escherichia coli 16.59 mm strong category.